Refurbishment And Upgrading The Different Types Of Motor Using Raspberry Pi - Sageman, Salmiyah (Universiti Sains Malaysia, 2017)
This project is to upgrade some type of motor to use Raspberry Pi. Some motors used are EDM machine DC servo motor, AC servo Denso robot, AC servo drive OTIS-LG and DC motor. Type of current used by the motor is a direct current (DC) and alternating current (AC). At School of Mechanical Engineering USM, there is an EDM machine (EDM Mitsubishi model M35J 1993) that have been damaged and the problem identified is the Z-axis cannot function properly. Although the machine was damaged but some of the mechanical parts of the machine can be used to upgrade the situation. But, after an observation is made, this machine cannot be upgraded because all the circuit has been disconnected and the machine does not have a complete manual. Next, the study continued using Denso robot arm but could not proceed because it has the same problem that does not have full use of the manual. Then, the study continued using OTIS-LG FDA 5000C Series servo drive with the main part are motor and driver. There are some modifications carried out on the driver's that suit the experiment conducted to drive the motor. Modifications were also made to the circuit to drive the motor by controlling the direction and speed of rotation. The Raspberry Pi program used in this study. After the experiments carried out, a modified driver cannot move to the intended direction and the speed of the motor cannot be controlled. Next, the research was replaced by a DC motor. The Raspberry Pi program is used in this study to control the direction and speed of rotation. DC motor will produce a pulse on each round and each pulse issued will be calculated.